José Braulio Da Silva Junior y Aline Saddi Chaves. “No logro leer lo que está escrito”. Una mirada discursiva y semiológica sobre el pichaçao en Campo Grande - MS (2018)
When facing a pichaçao on the walls of urban public spaces, untrained eyes will say: “I can not read what is written”, or even “unlike graffiti, the pichaçao does not represent relevant artistic meaning”. Pichaçao can even can be associated as an urban phenomenon of critical, social and cultural expression, a sort of counter-power (Foucault, 1979), but it will hardly be heard that “pichaçao is an art”, or that the plastic formation of a pichaçao has relevance amidst the other artistic expressions. This work intends to show the partial results of an ongoing research that has as object of study the pichaçao in the urban perimeter of the city of Campo Grande. Among the questions raised about the object we highlight its declarative functioning and its verbal-visual linguistic device. We work with the hypothesis that the scope of expression, namely the semiotic structure of the pichaçao, based on the spelling of the letters, can influence the scope of content at the level of the declaration as a process of generation of plastic meaning. When thinking about the formation of a process of generation of plastic meaning of the pichaçao, it should be kept in mind that the critical evaluation of a work such as music or painting involves taking into account certain parameters that legitimize, so to speak, the status of the artistic discourse in society. From this point of view, pichaçao could also be considered under its ethical (Bajtin, 2003), aesthetic and plastic aspect, so that a distinction the between the pichaçao and graffiti is possible. Based on these questionings, we support the hypotheses from two theoretical frameworks: plastic semiotics, which describes the semiotic structure of the pichaçao; and discourse analysis, theoretical discipline interested in the verbal articulation